PENGARUH PEMBELAJARAN BERBASIS MASALAH TERHADAP HASIL BELAJAR IPA DITINJAU DARI KEMAMPUAN BERPIKIR KRITIS - Ernawati Ernawati (Universitas Sarjanawiyata Tamansiswa, 2017)
The purpose of this study is to know the differences of the science study results of the 7th grade student of Taman Dewasa Ibu Pawiyatan Yogyakarta Junior High School on school year 2016/2017 among the uses of problem based learning with the conventional method that evaluated by the critical way of thinking of the students. The study is Quasi Experiment. The data are gathered with documented method, observation and test. The data analysis technic that used is Anacova test. The average of the science study results and the students’ critical way of thinking is higher than the conventional method. It means that there is an influence of the study problem based learning among the science study results of the 7th grade student of Taman Dewasa Ibu Pawiyatan Yogyakarta Junior High School on School Year 2016/2017 that evaluated by students’ critical way of thinking.